6. The Results of the Pisa Assessment in Dynamics in the Context of General Education in the Republic of Moldova - Crișciuc Viorica (Sciendo, 2023)
Through the reforms launched during 2009-2020 by the Ministry of Education, Culture and Research of the Republic of Moldova, in cooperation with development partners, they changed their emphasis in education in favor of quality and, respectively, the process of evaluating student results. Updating the National Curriculum made in accordance with the fundamental support Reference framework of the National Curriculum, Basic Curriculum: competency system for general education, analytical support School curriculum evaluation report, etc. and the managerial support provided by the Ministry of Education, Culture and Research of the Republic of Moldova, favored a modern educational system with obvious results in national evaluations.